Kościół wędrowniczek - Zarębczan, Władysław (Zeszyty Wiejskie, 2019)
The purpose of the article is to present the history of the “wandering church” in Mętków, which shows on a microscale the strength of colloquial religiosity and religious culture in one of the small local communities in Poland. The biography of Pope John Paul II entered the history of this church, which is why it has the status of a church-relic for the faithful people, which is another interesting interpretative context.